2016
DOI: 10.1016/j.pep.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding peptide as a novel affinity tag for purification of recombinant proteins

Abstract: Purification of recombinant proteins constitutes a significant part of the downstream processing in biopharmaceutical industries. Major costs involved in the production of bio-therapeutics mainly depend on the number of purification steps used during the downstream process. Affinity chromatography is a widely used method for the purification of recombinant proteins expressed in different expression host platforms. Recombinant protein purification is achieved by fusing appropriate affinity tags to either N- or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The NT‐11 tag enhanced the soluble production of all tested proteins, which were also His‐tagged. Moving up to fusion tags of higher molecular mass, the Kumar lab designed a 34‐amino acid heparin‐binding affinity tag (HB‐tag) . HB‐tagged proteins can be purified using a heparin‐agarose resin under naturing or denaturing conditions.…”
Section: Advances In Plasmid Designmentioning
confidence: 99%
“…The NT‐11 tag enhanced the soluble production of all tested proteins, which were also His‐tagged. Moving up to fusion tags of higher molecular mass, the Kumar lab designed a 34‐amino acid heparin‐binding affinity tag (HB‐tag) . HB‐tagged proteins can be purified using a heparin‐agarose resin under naturing or denaturing conditions.…”
Section: Advances In Plasmid Designmentioning
confidence: 99%
“…Costa et al 2014;Yadav et al 2016). Nevertheless, novel tags, from natural origin (Li et al 2016) or rationally designed (Morris et al 2016), are continually being reported in the literature. Among the affinity tags recently described, interesting alternatives to the His-tag have been presented (Vargas-Cortez et al 2016;Cantu-Bustos et al 2016).…”
Section: Tag-dependent Purificationmentioning
confidence: 99%
“…Some of the common putative heparin-binding segments are XBBXBX, XBBBXXBX, and XBBXXBBBXXBBX, where B is one of the three basic amino acids (mainly arginine and lysine) and X is any of the other 17 natural amino acids. These heparin binding segments function by electrostatic interaction with the negatively charged sulfate and carboxyl groups in heparin or heparan sulfate [19].…”
Section: Introductionmentioning
confidence: 99%